Contextual cueing effects despite spatially cued target locations - Schankin, Andrea; Schubö, Anna (Psychophysiology, 2010)
Reaction times (RT) to targets are faster in repeated displays relative to novel ones when the spatial arrangement of the distracting items predicts the target location (contextual cueing). It is assumed that visual-spatial attention is guided more efficiently to the target resulting in reduced RTs. In the present experiment, contextual cueing even occurred when the target location was previously peripherally cued. Electrophysiologically, repeated displays elicited an enhanced N2pc component in both conditions and resulted in an earlier onset of the stimulus-locked lateralized readiness potential (s-LRP) in the cued condition and in an enhanced P3 in the uncued condition relative to novel displays. These results indicate that attentional guidance is less important than previously assumed but that other cognitive processes, such as attentional selection (N2pc) and response-related processes (s-LRP, P3) are facilitated by context familiarity.